Carbon Emission Disclosure and Moderating Role of Education Background of Board of Director - Ma'wa, 'Afifah; Sutopo, Bambang (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 1 (2025): Jurnal Online Insan Akuntan (Juni 2025), 2025)
This study aims to prove the influence of company characteristics on carbon emission disclosure (CED) practices. This study uses a quantitative approach with a panel data regression analysis method. The research sample consists of 312 transportation and logistics sector companies listed on the Indonesia Stock Exchange (IDX) during 2017-2023. The results showed that company age has a significant positive effect on CED. On the other hand, the economic and business education background of the directors proved to strengthen the relationship between company age and CED. The results of this study contribute to the improvement of environmental disclosure performance in Indonesia where younger companies are expected to adopt best practices from more established companies, especially in terms of environmental transparency practices. On the other hand, management may consider selecting directors with a background in economics and business education with the aim of increasing corporate awareness and responsibility in carbon emissions disclosure.   Keywords : Carbon Emission Disclosure, Disclosure, Corporate Governance, Company Age, Education Background